PENGARUH LAMA FERMENTASI ALAMI SECARA AEROB CAIRAN PULPA HASIL SAMPING FERMENTASI BIJI KAKAO TERHADAP KARAKTERISTIK CUKA FERMENTASI - Puspa Aridona, Made; Wartini, Ni Made; Arnata, I Wayan (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 3 No 3 (2015): September)
Watery sweating is the liquid produce during process of cocoa fermentation. The liquid contains alcohol that it could be a substrat to produce higher acetic acid. In this research, the natural aerobic fermentation was carried out to produce cocoa vinegar. The oxygen supply was done by process of aeration using aerator. The aim of the research were to determine the influence of fermentation time on the characteristics of cocoa vinegar and to find out the fermentation time for producing cocoa vinegar with the best characteristics. The experiment was designed by simple Randomized Block Design. The treatment of fermentation time that experimented consists of 11 levels, namely 0, 1, 2, 3, 4, 5, 6, 7, 8, 9, and 10 days. The result showed that the natural aerobic fermentation time influenced the content of acetic acid, pH, and total soluble solid of cocoa vinegar. The best characteristics of cocoa vinegar was produce after 6 days fermentation. Acetic acid content of the cocoa vinegar was 2,30% with the vinegar pH and total soluble solid was 3,27 and 5,0 %brix, respectively.
Keywords: 60,